Pengaruh Hubungan Pelanggan Terhadap Loyalitas Pelanggan ( Studi Kasus PT.Krida Dinamika Autonusa Bima ) - Ika Melisa; Intisari Haryanti (Journal of Business and Economics Research (JBE), 2020)
This study aims to determine the significant influence of customer relations on customer loyalty (Case study of PT. Krida Dinamika Autonusa Bima) research method namely the type of associative research using quantitative data from primary data sources. The population in this study are consumers who have visited more than once at PT. Krida Dinamika Autonusa Bima whose number is not known with certainty by the sampling technique used is Purposive sampling with the formula unknown polulations so that the study sample is obtained 96 customers, all samples are given a questionnaire using a Likert scale. Data collection techniques used are observation, interviews, and questionnaires with data analysis techniques that are validity, reliability, simple linear regression analysis, simple correlation and hypothesis testing (t test). From the results of processing and testing the hypothesis shows the value of t arithmetic amounting to -3.140> t table 1.985 and a significant level (sig)> 0.05 that is 0.002 <0.05, meaning that there is a negative and significant influence of Customer Relations on Customer Loyalty at PT. Krida Dinon Autonusa-Bima. From the results of the determination test addressed the effect of Customer Relations on Customer Loyalty at PT. Krida Dinon Autonusa-Bima is 30.8% while the remaining 60.2% is influenced by other factors not examined in this study.